Awareness of child visual status among parents with primary school children in Puncak Alam / Nur Atiqah Azmi - Azmi, Nur Atiqah (Faculty Of Health Sciences, 2015)
The purpose of this study was to investigate the awareness of child visual status among parents with primary school children in Puncak Alam. Method: A set of questionnaire were given to respondents who fulfilled the inclusion criteria. Distribution of questionnaire were held around Puncak Alam area among parents with primary school children. They will be given one week to fill the questionnaire. After that, they need to put answered questionnaire into the mailbox that will be collected by examiner. In this study, 80 of respondents has been participated which comprised of 48 female and 32 male aged 25 to 56 years old. The questionnaire includes Part A with 6 questions (demographic data), Part B with 8 questions (medical and ocular history) and Part C (knowledge of eye disease and refractive error) with 17 questions. Respondents need to answer all questions. Result: Sixty one from eighty respondents were aware with their children visual status (76.3%) while 19 of them did not aware with their children problem (23.7%). Majority of parents had taken their children for school entrance medical check up with total of 32 (40%) while the rest of them did not bring their children for medical check up (60%). From 32 respondents who bring their children for school entrance medical check up, only 28 of them had their children's eyes screened (35%) and 4 of them did not have their children's eyes screened during the check up (5%). 73 (91.3%) respondents think that it is necessary for their children to get eye examination annually and while the rest of them think it is unnecessary for their children to get an eye check up annually. Respondents were asked about their knowledge of eye disease and refractive error. Most of them know about refractive error such as farsightedness (hyperopia),nearsightedness (myopia), glaring (astigmatism) and squint (strabismus). However, out of 80 respondents, only 32 of them know about lazy eye (amblyopia) which contributed to 40% and largely of them (60%) do not know about amblyopia. All respondents agreed 100% that it is important for their children to have good vision during school years. Conclusion: Awareness of visual status should be emphasized among parents to decrease the percentage of getting visual impairment among children. If refractive error and eye disease can be screened earlier, it has significant amount in reducing prevalence and severity of visual impairment in children.